Banks in Distress : The Case of Bangladesh. (IMF Working Papers; Working Paper, 1990)
This paper describes the situation of bank distress which developed in Bangladesh since 1983-84. Since the key problem banks are state-owned, there has been no banking crisis, although costs to the economy have been high. Main causes of distress included preferential and directed lending, and administered interest rates. Inadequate supervision and managerial weaknesses were other contributory factors. Macroeconomic trends played a small role only. The authorities have recently taken major corrective measures. The paper calls for determination in the implementation of these measures to swiftly restore financial stability and limit the overall cost of this long-running distress situation.